PENGARUH WORK LIFE BALANCE, KNOWLEDGE MANAGEMENT, DAN QUALITY OF WORK LIFE TERHADAP EMPLOYEE ENGAGEMENT DI PT BHINNEKA MENTARI DIMENSI - Katrin Patricia Putri (2023)
This quantitative research aims to investigate the influence of work life balance, knowledge management, and quality of work life on employee engagement. The study was conducted on 80 permanent employees in the operational department of PT Bhinneka Mentari Dimensi. The sampling technique used in this study was simple random sampling. The data was collected through an online questionnaire via Google Form and analyzed using the Partial Least Square (PLS) method. The following results were obtained from the tests in this study: (1) work life balance has a positive and significant effect on employee engagement at PT Bhinneka Mentari Dimensi, (2) knowledge management has a positive and significant impact on employee engagement at PT Bhinneka Mentari Dimensi, and (3) quality of work life has a positive and significant impact on employee engagement at PT Bhinneka Mentari Dimensi.